2012
DOI: 10.1177/1352458511434607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D3 supplementation on relapses, disease progression, and measures of function in persons with multiple sclerosis: exploratory outcomes from a double-blind randomised controlled trial

Abstract: Supplementation with 20,000 IU vitamin D(3) weekly did not result in beneficial effects on the measured multiple sclerosis-related outcomes. This study was not powered to address clinical outcomes, but none of the results were suggestive of an effect in this unselected population of fully ambulatory persons with multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 32 publications
5
140
1
3
Order By: Relevance
“…The current research based on large datasets is being targeted on using vitamin D supplementation as an alternative approach for MS treatment; however, there is still lack of convincing evidence for its effect on disease progression (80). The exact mechanism governing vitamin D-mediated regulation of immune response has to be completely elucidated for exploiting it as a future treatment option for MS.…”
Section: Vitamin D As a Future Treatment Option For Msmentioning
confidence: 99%
“…The current research based on large datasets is being targeted on using vitamin D supplementation as an alternative approach for MS treatment; however, there is still lack of convincing evidence for its effect on disease progression (80). The exact mechanism governing vitamin D-mediated regulation of immune response has to be completely elucidated for exploiting it as a future treatment option for MS.…”
Section: Vitamin D As a Future Treatment Option For Msmentioning
confidence: 99%
“…In patients with MS living in temperate and Nordic countries, as in the general populations of these countries, vitamin D insufficiency is widespread, whatever the cutoff (50 or 75 nmol/ liter) for the lower limit of the 25-OH-D serum level ( Figure 3): indeed, as early as the earliest stages of the disease, that is, in patients with clinically isolated syndrome (CIS) or with RRMS, average serum levels are between 42 and 74 nmol/ liter, depending on the studies and the seasons, with a general mean close to 60 nmol/liter [SoiluHänninen et al 2005[SoiluHänninen et al , 2012Smolders et al 2008b;Hiremath et al 2009;Kragt et al 2009;Mowry et al 2010;Pierrot-Deseilligny andSouberbielle, 2010, 2012;Simpson et al 2010;Banwell et al 2011;Dabbaghmanesh and Yousefipour, 2011;Lonergan et al 2011;Neau et al 2011;Steffensen et al 2011;Yildiz et al 2011; Bäärnhielm Kampman et al 2012;Kirbas et al 2012;Løken-Amsrud et al 2012;Moen et al 2012;Runia et al 2012;SoiluHänninen et al 2012;Šaltyte . Benth et al 2012;Triantafyllou et al 2012] (Table 1).…”
Section: Vitamin D Requirements and Insufficiencymentioning
confidence: 99%
“…Conversely, another study of comparable size showed a significant and pronounced effect of 14,000 IU vitamin D3 per week on new gadolinium-enhancing lesions after 1 year [14]. The first study included only clinical end points, and the pre-study relapse rate was only 0.11 [13]. The study was therefore obviously underpowered to detect any realistic effect on relapses of any intervention, including vitamin D.…”
Section: Can Vitamin D Reduce Inflammation In Relapsing-remitting Mulmentioning
confidence: 99%
“…It is generally accepted that the trials published so far have been too small and methodologically divergent to be conclusive [12]. Thus, one study comprising 68 patients randomized to placebo or 20,000 IU vitamin D3 per week for 2 years were completely negative, although mean serum 25(OH)D more than doubled to 121 nmol/l in the intervention group [13]. Conversely, another study of comparable size showed a significant and pronounced effect of 14,000 IU vitamin D3 per week on new gadolinium-enhancing lesions after 1 year [14].…”
Section: Can Vitamin D Reduce Inflammation In Relapsing-remitting Mulmentioning
confidence: 99%